Major lake level fluctuations and climate changes for the past 16,000 years as reflected by diatoms and chironomids preserved in the sediment of Laguna Potrok Aike, southern Patagonia - Massaferro, Julieta; Recasens, C.; Larocque Tobler, I.; Zolitschka, B.; Maidana, Nora Irene (Quaternary Science Reviews)
Laguna Potrok Aike is a maar lake located in southernmost Argentina and is one of the few permanent lakes preserving a continuous climatic record from the semiarid Patagonian steppe. Furthermore, its location close to Antarctica provides a unique opportunity to compare paleoclimate from continental South America with the polar records. The analysis of subfossil chironomids and diatoms throughout a 16-m sedimentary record retrieved from this lake, combined with a well-constrained chronology of the last ca 16 ka BP, provided a high resolution paleoenvironmental reconstruction of the limnology of the lake and regional climate conditions. The combination of both bioproxies showed humid conditions during the Lateglacial, followed by drier conditions during the Holocene, resulting in large variations in lake level. Despite not showing a clear evidence of a cold reversal similar to the Antarctic Cold Reversal and/or the Younger Dryas, both records suggest high water levels and oligotrophic conditions between 16.4 and 11.5 cal. ka BP. The lake level drop that occurred at ca 8.7 ka BP is well documented by both bioproxies. Fil: Massaferro, Julieta. Administración de Parques Nacionales. Delegación Regional Patagonia; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Recasens, C. University of Geneva; Suiza Fil: Larocque Tobler, I. Limnology and Paleolimnology Services; Suiza Fil: Zolitschka, B. Universitat Bremen; Alemania Fil: Maidana, Nora Irene. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina